Model Analisis Penyebab Rendahnya Penguasan Konsep Yang Diuji Dalam Ujian Nasional (Kajian Pada Materi Ilmu Kimia Pada Siswa SMA/MA Sekitar Kampus Unsyiah) - Muhammad Adlim; Intan Wilyta; Muhammad Hasan (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2017)
This article aims to discuss a model for the learning difficulty analysis of senior high school students in the field of chemistry. The study was focus on senior high schools (SMA/MA) located around the campus of Syiah Kuala University. They were SMAN 5 Banda Aceh, SMAN 1 Krueng Barona Jaya, SMAN 1 Baitussalam, MA Rukoh, and MA Darussalam. The Student scores of National Examination (UN) from 2008-2010 were analyzed to find the chemistry topics that most student failed to answer and the frequency failure occurred among the subject schools in three times national examination (2008, 2009 2010). The validated questionnaire was distributed to teachers and students to explore the causes and solutions for low mastery concepts among the students. Using this analysis model, it is found that the concept of acids and bases, thermochemistry, solubility and the corrosion concepts were the highest frequently and consistently fail to master by students in the sampled schools. Majority responses from students and teachers were consistent with the data finding from UN data analysis. Low student mastery on those chemistry topics becuase students fail to interpretation of pH indicator diagram and corrosion experiment drawing. To overcome the student weakness was suggested to improve the learning process, to discuss the low mastery topic in teacher regular group discussion (MGMP). Majority respondents also suggested to provide training and problem-solving, and enrich the teaching materials containing chemical topics that were difficult to be mastered by students